The contemporary churches in the natural environment: modernization of landscape traditions - Sleptsov, Oleg; Ivashko, Yulia; Dmytrenko, Andrii; Krupa, Michał (Landscape Architecture and Art, 2021)
The article analyzes and formulates the characteristic features of traditional Ukrainian landscape design, which had authentic roots and was based on minimal interference in the existing natural environment and its maximum use to enhance the properties of architecture. The purpose of the article is to identify traditional and innovative elements in the landscaping of modern Ukrainian Orthodox churches.The descriptive method, the graphical-and-analytical method, the methods of historical and comparative analysis were used. The main traditional methods of Ukrainian landscape design of the XVII–XVIII centuries are determined. Examples of traditional landscape design of Polish monasteries are given, taking into account the rather long influence of Polish culture on a large part of Ukrainian territories. The modern landscape techniques in Ukraine based on the use of folk traditions are described and analyzed. Two main directions of modern landscape design of territories around cult buildings are defined – repetition of the established receptions (in ethno-complexes) and creative modernization of architectural forms in combination with landscape design (on examples of newly built churches). It is shown how both methods enhance the properties and aesthetic expressiveness of architecture.